The tribal structure and traditional institutions of Kazakh society are key determinants of survival and social stability - Kazhenova , Гульнар (Turkic Studies Journal, 2025)
This article provides a comprehensive analysis of traditional governance and social organization institutions in Kazakh society, tracing their origins to the formation of nomadic communities. These institutions are examined as effective mechanisms for ensuring survival and maintaining social resilience during periods of systemic crisis. The relevance of this study is determined by the necessity to address an existing imbalance in historiography, whereby the examination of external influences – such as Russian colonial policies and Soviet modernization – while paying less attention to the internal adaptive mechanisms that evolved within the framework of centuries-old nomadic traditions. This shift in research perspective allows nomadic societies to be viewed as active agents endowed with sophisticated systems of internal regulation, rather than as passive subjects of historical processes. The research is grounded in an interdisciplinary synthesis that integrates the methodological approaches of history, historical anthropology, and sociology. The study’s theoretical framework is informed by the concept of the ‘moral economy’, which emphasizes the norms of reciprocity, solidarity, and collective ethics of survival. It also draws upon the theory of social resilience, which interprets traditional institutions not as static or archaic remnants, but as dynamic and flexible adaptive systems that ensure the continuity of social structures and the transmission of cultural codes. Within this theoretical framework, the article provides a detailed analysis of the tribal structure of Kazakh society, presenting it as a multi-level, hierarchical system that performs functions of social support, protection, and self-regulation. Particular attention is given to the institutions of mutual aid – asar, zhylu and sauyn – which are conceptualized as practical manifestations of the principles of the ‘moral economy’. These institutions constituted an effective system of collective insurance against vital risks and facilitated the redistribution of scarce resources. The roles of biys and aksakals are also examined, as they functioned as meritocratic mechanisms for dispute resolution and maintenance of legal order based on customary law (adat), thereby ensuring internal stability and social equilibrium. The scientific novelty of the study lies in its capacity to transcend the limitations of traditional historiography, demonstrating that traditional institutions with deep historical roots provided comprehensive protection, ranging from the physical survival of individuals to the preservation of cultural identity. A key finding of the research is that the systemic crisis resulting from the violent disruption of these institutions during the colonial and Soviet periods underscores their crucial role in maintaining the cohesion and continuity of Kazakh society over the centuries. The practical significance of the findings lies in the potential application of the identified models of social resilience to comparative analyses of adaptive strategies in diverse traditional societies across Eurasia, which are currently facing the challenges posed by globalization, climate change and socio-economic transformations in the contemporary era.